2009
DOI: 10.1007/s10517-010-0777-7
|View full text |Cite
|
Sign up to set email alerts
|

Study of Monarda Fistulosa Essential Oil as a Prospective Antiseborrheic Agent

Abstract: Monarda fistulosa essential oil characterized by pronounced therapeutic effects is proposed for the treatment of seborrhea. Studies of its antibacterial, antimycotic, and antiinflammatory activities showed that it inhibits microorganism growth and is superior to hydrocortisone in combination with vitamin B6 by its antiinflammatory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…ex Lag. , and M. punctata L. ( Fraternale et al, 2006 ; Zhilyakova et al, 2009 ; Geffre et al, 2011 ; Tabanca et al, 2013 ; Thompson et al, 2013 ; Li et al, 2014 ; Mattarelli et al, 2017 ; Shanaida et al, 2018b ; Deepika et al, 2020 ; Ghosh et al, 2020 ; Marchioni et al, 2020 ).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…ex Lag. , and M. punctata L. ( Fraternale et al, 2006 ; Zhilyakova et al, 2009 ; Geffre et al, 2011 ; Tabanca et al, 2013 ; Thompson et al, 2013 ; Li et al, 2014 ; Mattarelli et al, 2017 ; Shanaida et al, 2018b ; Deepika et al, 2020 ; Ghosh et al, 2020 ; Marchioni et al, 2020 ).…”
Section: Introductionunclassified
“…Flambeau Ojibwe dried the whole aerial part of this plant and boiled it in a suitable vessel to obtain the essential oil for treatment of bronchial and catarrh conditions through inhalation ( Wagner, 2006 ). Later, it was found that M. fistulosa essential oil is the natural source of thymol and p -cymene with strong antiseptic properties ( Zhilyakova et al, 2009 ; Mattarelli et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils of Monarda species have been reported to be rich in oxygenated monoterpenes, leading to differentiation into the following chemotypes: thymol, carvacrol, borneol, and geraniol [ 10 ]. A literature survey regarding biological activities of the Monarda species essential oils and their major compounds, based on references [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], is summarized in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Some kind of essential oils exhibited anti-oxidant [ 11 , 12 ], anti-hypoxic-ischemic [ 13 ], anti-bacterial and anti-fungal activities [ 14 ] muscle relaxant [ 15 ]. Lavender essential oil, volatile aromatic oily liquids isolated from Lavandula plants by various means, used as folk medicine possesses many therapeutic properties including anti-oxidant [ 16 ], antiinflammatory [ 17 ], antibacterial [ 18 ], anxiolytic and sedative action [ 19 ], antiplatelet and antithrombotic activities [ 20 ], antimutagenic activity [ 21 ], treatment agitation in patients with severe dementia [ 22 ]. But the protective effects of lavender oil against cerebral ischemia/reperfusion damage have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%